Found Opportunities for Social Participation: Facilitating Inclusion of Adults With Aphasia. Issue 1 (January 2017) - Howe, Tami
Abstract : Lack of communicatively supportive opportunities for social participation is a critical barrier for many people with aphasia. Speech–language pathologists need to address this barrier by playing a key role in ensuring that adults with aphasia have appropriate social participation choices in their communities. Speech–language pathologists may provide these services themselves or may draw on their unique expertise in communication and aphasia to work with people with aphasia, family, friends, other health care professionals, and disability support organizations to advocate for and/or develop opportunities. This article provides examples of specific approaches that can help achieve this important goal in relation to 4 levels of social participation: interacting with others without doing a specific activity with them (e.g., having satisfying conversations), interacting with others during activities in which there is a common goal (e.g., participating in enjoyable recreational activities), interacting with others to help a specific person or group of people (e.g., volunteering), and interacting with others to make a contribution to society (e.g., being involved in an aphasia advocacy organization).